EDUKASI PASAR MODAL DALAM RANGKA MENINGKATKAN LITERASI KEUANGAN BAGI KALANGAN MAHASISWA UNIVERSITAS SINGAPERBANGSA KARAWANG - Nopiana, Medi; Permana, Fikri C.; Ariyani, Risma; Anggraini, Alvira; Rahma, Amelia (Politeknik Perkeretaapian Indonesia Madiun, 2025)
The financial literacy program is an effort made by the Financial Services Authority to direct the community to manage their finances better. This is expected to improve the welfare of the community itself. Meanwhile, community service activities that overlap with the program, including organizing capital market education activities, particularly for students of Universitas Singaperbangsa Karawang, are still very lacking. Therefore, the community service team of Universitas Singaperbangsa Karawang took the initiative to carry out the capital market education activity. This activity was held online on Tuesday, November 26, 2024, and attended by 68 students of the university's Bachelor's degree in Management. The method of implementing the activity used a general lecture format. This activity provides conclusions regarding the motivation of students to invest in the capital market. The message that can be taken from this activity is that anyone (including students) can start investing in the capital market without limitations, anytime and anywhere, with any nominal amount. The key is that students must possess a strong willingness and the ability to analyze investment products, ensuring that opportunities for optimal returns remain open while maintaining a well-managed risk profile.